Self reported dental health attitudes and behaviour of dental students in Turkey - (:unkn) unknown (My University, 2011)
OBJECTIVES: The aim of this study was to compare the differences in self-reported oral health attitudes and behaviour between preclinical and clinical dental students in Turkey using Hiroshima University Dental Behavioural Inventory (HU-DBI). METHODS: A Turkish version HU-DBI questionnaire with additional 7 questions, totally 27 items, was distributed among 1022 dental students. RESULTS: The response rate was 75% (486 preclinical and 278 clinical students). Significantly higher (P=0.000) percentage of the preclinical students, compared to clinical students, worry about colour of their teeth, are bothered by the colour of their gums, put off going to the dentist until they have a toothache; think that their teeth are getting worse despite their daily brushing, it is impossible to prevent gum disease with tooth brushing alone, and they cannot help having false teeth when they are old. Moreover, the preclinical students more frequently agree on that their gums tend to bleed when they brush their teeth, they use a toothbrush which has hard bristles, and they don't feel they've brushed well unless with strong strokes (P=0.000). However, a higher proportion of clinical students compared to preclinical students brush each of their teeth carefully, think that they can clean their teeth without using toothpaste, have had their dentist tell them that they brush very well (P=0.000). The HU-DBI score of clinical students (7.47±1.86) was significantly (P=0.000) higher than preclinical students (6.00±1.86). CONCLUSIONS: Dental students should have a comprehensive program, including their self-care regimes, starting from their first year of education.
Keywords: Turkey; Dental students; HU-DBI; Oral health attitudes and behavior